CONDICIONES QUE MODIFICAN LA PERMEABILIDAD DE LOS VASOS CEREBRALES - OBRADOR ALCALDE, S; ALVAREZ, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Opaque material is passed through a catheter directly into the right heart Arm-to-tongue circulation time helps to determine when X-ray exposure should be made By this method parts of the lesser circulation can be seen, one uncomplicated by another The
BOL INST ESTUD MED BIOL
Keywords: CONDICIONES, MODIFICAN, PERMEABILIDAD, CEREBRALES; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA